Altered microbial structure and function after thermokarst formation. (26th November 2020) - Liu, Futing; Kou, Dan; Chen, Yongliang; Xue, Kai; Ernakovich, Jessica G.; Chen, Leiyi; Yang, Guibiao; Yang, Yuanhe
Abstract: Permafrost thaw could induce substantial carbon (C) emissions to the atmosphere, and thus trigger a positive feedback to climate warming. As the engine of biogeochemical cycling, soil microorganisms exert a critical role in mediating the direction and strength of permafrost C‐climate feedback. However, our understanding about the impacts of thermokarst (abrupt permafrost thaw) on microbial structure and function remains limited. Here we employed metagenomic sequencing to analyze changes in topsoil (0–15 cm) microbial communities and functional genes along a permafrost thaw sequence (1, 10, and 16 years since permafrost collapse) on the Tibetan Plateau. By combining laboratory incubation and a two‐pool model, we then explored changes in soil labile and stable C decomposition along the thaw sequence. Our results showed that topsoil microbial α‐diversity decreased, while the community structure and functional gene abundance did not exhibit any significant change at the early stage of collapse (1 year since collapse) relative to non‐collapsed control. However, as the time since the collapse increased, both the topsoil microbial community structure and functional genes differed from the control. Abundances of functional genes involved in labile C degradation decreased while those for stable C degradation increased at the late stage of collapse (16 years since collapse), largely driven by changes in substrate properties along the thaw sequence. Accordingly, faster stable C decomposition occurred at the late stage of collapse compared to the control, which was associated with the increase in relative abundance of functional genes for stable C degradation. These results suggest that upland thermokarst alters microbial structure and function, particularly enhances soil stable C decomposition by modulating microbial functional genes, which could reinforce a warmer climate over the decadal timescale. Abstract : Based on the metagenomic sequencing, this study analyzed the impacts of thermokarst (abrupt permafrost thaw) on topsoil microbial communities and functional genes along a thaw sequence on the Tibetan Plateau. Our results revealed that, although thermokarst‐induced changes in soil environment, substrates and vegetation properties could all regulate microbes, substrate properties mainly drove the shifts in microbial structure and function. Particularly, thermokarst formation stimulated functional genes associated with soil stable carbon degradation, and enhanced soil stable carbon decomposition. These results highlight that thermokarst formation could alter microbial structure and function over the decadal timescale.